Dose escalated intensity modulated radiotherapy in the treatment of cervical cancer. Issue 1 (December 2015) - Cihoric, Nikola; Tsikkinis, Alexandros; Tapia, Coya; Aebersold, Daniel; Zlobec, Inti; Lössl, Kristina
Abstract Purpose Standard dose of external beam radiotherapy seems to be insufficient for satisfactory control of loco-regionally advanced cervical cancer. Aim of our study is to evaluate the outcome as well as early and chronic toxicities in patients with loco-regionally advanced cervical cancer, treated with dose escalated intensity modulated radiotherapy (IMRT) combined with cisplatin chemotherapy. Material and methods Thirty-nine patients with cervical carcinoma FIGO stage IB2 – IVA were treated with curative intent between 2006 and 2010. The dose of 50.4 Gy was prescribed to the elective pelvic nodal volume. Primary tumors < 4 cm in diameter (n = 6; 15.4 %) received an external beam radiotherapy (EBRT) boost of 5.4 Gy, primary tumors > 4 cm in diameter (n = 33; 84.6 %) received an EBRT boost of 9 Gy. Patients with positive lymph nodes detected with18 FDG-PET/CT (n = 22; 56.4 %) received a boost to a total dose of 59.4 - 64.8 Gy. The para-aortic region was included in the radiation volume in 8 (20.5 %) patients and in 5 (12.8 %) patients the para-aortic macroscopic lymph nodes received an EBRT boost. IMRT was followed with a 3D planned high dose rate intrauterine brachytherapy given to 36 (92.3 %) patients with a total dose ranging between 15–18 Gy in three fractions (single fraction: 4–6.5 Gy). Patients without contraindications (n = 31/79.5 %) received concomitantly a cisplatin-based chemotherapy (40 mg/kg) weekly. Toxicities were graded according to the common terminology criteria for adverse events (CTCAE v 4.0). Results Mean overall survival for the entire cohort was 61.1 months (±3.5 months). Mean disease free survival was 47.2 months (±4.9 months) and loco-regional disease free survival was 55.2 months (±4.4 months). 65 % of patients developed radiotherapy associated acute toxicities grade 1, ca. 30 % developed toxicities grade 2 and just two (5.2 %) patients developed grade 3 toxicities, one acute diarrhea and one acute cystitis. 16 % of patients had chronic toxicities grade 1, 9 % grade 2 and one patient (2.6 %) toxicities grade 3 in the form of vaginal dryness. Conclusion Dose escalated IMRT appears to have a satisfactory outcome with regards to mean overall survival, disease free and loco-regional disease free survival, whereas the treatment-related toxicities remain reasonably low.